2016
DOI: 10.3748/wjg.v22.i38.8631
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic carcinoma of the pancreas: Case report and literature review of reported cases in Japan

Abstract: We report a case of a 64-year-old woman with anaplastic carcinoma of the pancreas (ACP) with cyst formation and review 60 ACP cases reported in Japan. In 20% of cases, laboratory tests revealed severe anemia (hemoglobin level < 10.0 g/dL) and elevated leucocyte counts (> 12000/mm3), which were likely attributable to rapid tumor growth, intratumoral hemorrhage, and necrosis. Elevated serum CA19-9 levels were observed in 55% of cases. Cyst-like structures were observed on imaging in 47% of cases, and this findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 16 publications
2
42
0
1
Order By: Relevance
“…ACP represents 0.1% of malignant exocrine pancreatic tumors according to one study, with autopsy series revealing higher incidences . It has a clinical presentation similar to PDAC, such as jaundice and abdominal pain; however, at time of diagnosis a bulky tumor is frequently detected, with involvement of organs in the vicinity . It tends to present more commonly in men versus women with a ratio of 2.5:1, and occurs more frequently in the head of the pancreas, with an average size of 4 cm …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ACP represents 0.1% of malignant exocrine pancreatic tumors according to one study, with autopsy series revealing higher incidences . It has a clinical presentation similar to PDAC, such as jaundice and abdominal pain; however, at time of diagnosis a bulky tumor is frequently detected, with involvement of organs in the vicinity . It tends to present more commonly in men versus women with a ratio of 2.5:1, and occurs more frequently in the head of the pancreas, with an average size of 4 cm …”
Section: Discussionmentioning
confidence: 99%
“…One case series of ACP reported that four out of five patients (80%) were diagnosed with ACP on EUS‐FNA . Another series reported that only three out of 60 patients (5%) were diagnosed preoperatively with ACP using EUS‐FNA . This highlights the importance of integrating the clinical and radiological findings with cytomorphology to arrive to the most accurate diagnosis possible, in the setting of an EUS‐FNA of a pancreatic mass .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations